Progressive Decline of Partial Pressure of Carbon dioxide and Bicarbonate levels in Arterial Blood of Pregnant Women - Sunyal, Dipok Kumar; Amin, Md Ruhul; Molla, MH; Talukder, MA Momen; Ahmed, Abida; Begum, Momotaj (Journal of Bangladesh Society of Physiologist, 2009)
Â In the present study the partial pressure of carbon dioxide (PaCO2) and bicarbonate ion (HCO3-) in arterial blood was estimated in 32 women in Dhaka city. For this purpose a total 32 women subjects with age ranged from 25 years to 35 years without any recent history of respiratory diseases were selected and divided into 8 healthy non-pregnant women as control and 24 normal pregnant women as experimental group. Experimental group was further divided into 8 first trimester, 8 second trimester & 8 third trimester of pregnant women. The PaCO2 and HCO3- were estimated by using "Easy Blood Gas Auto Analyzer". The PaCO2 and HCO3- were estimated during the 1st, 2nd, 3rd trimesters of pregnant women and non-pregnant women. The mean of measured values of PaCO2 and HCO3-were analyzed statistically in relation to 1st, 2nd, 3rd trimesters of pregnant women & non-pregnant women. The PaCO2 and HCO3- were significantly lower in 1st trimester, 2nd trimester & 3rd trimester of pregnant women than that of non-pregnant women. There were no statistically significant difference of PaCO2 and HCO3- between the 1st trimester and 2nd trimester; between the 1st trimester and 3rd trimester; and between the 2nd trimester and 3rd trimester of pregnant women. It may be concluded that the causes of progressively decreased PaCO2 and HCO3- throughout the pregnancy were most likely to be due to effect of progesterone causing hyperventilation. Hyperventilation in pregnancy is due to hypersensitivity of respiratory centre. Due to hyperventilation, there is expelling out CO2 and HCO3- causing decreases PaCO2 and HCO3- during pregnancy. doi: 10.3329/jbsp.v3i0.1788 J Bangladesh Soc Physiol.2008 Dec;(3):13-16.